UPAYA GURU PAI DALAM MENUMBUHKAN KARAKTER SISWA MELALUI MATA PELAJARAN AQIDAH AKHLAQ DI MTs. RAUDLATUL ULUM KARANGPLOSO MALANG - Farhan Miladi; Chalimatus Sa’diyah; Nur Hasan (VICRATINA, 2021)
Education is a container inherit and develop the knowledge, skills and expertise. Throught education most human can develop the potential and improve the level of live of them. Islam education is one of the siences that is always present in the education curriculum in Indonesia. Education of Islam aims to prepare students to believe, understand and practice the teaching of Islam throught the activities of learning, guidance or training. The reasearch is aimed to describe the character of discipline, motivation and interest in learning the students throught the subjects of aqidah akhlaq in MTs. Raudlatul Ulum Koarangploso Malang. In addition it is also to describe the obstacles thet experience by teachers in foster discipline, motivation and interest learning aqidah akhlaq along with the solution in MTs. Raudlatul Ulum Karangploso Malang. Research is using approach qualitative to perform retrieval of data throught observation, interviews0and0documentation.0The research0was conducted on students in MTs. Raudlatul Ulum Karangploso Malang. Results of the research were obtained by exposure to a resource, the efforts of teachers PAI in foster character discipline, motivation and interest in learning the students throught of subjects aqidah akhlaq in MTs. Raudlatul Ulum Karangploso Malang by way of peparing a plan of learning, creating an atmosphere that is pleasant in activity learning teaching, using the method of teaching that is not boring or varied, giving assigments to students, provide asseement or evaluation and give praise. The constraints are understood better by the teachers to foster an attitude of discipline, motivation and interest in learning is the lack of support from the parents of students to spur the spirit of0learning., the influence0of environment ot the0association of students at home, the influence of the gadgetor handphone and are not too interest with lessons of aqidah akhlaq.Key words : Character discipline, motivation, interest in learning.